Implementation of Black-Box Testing on the Information System for the Smart Indonesia Card College Recommendation - Sholehurrohman, Ridho; Qurrota A’yuni, Salsabila; Sabda Ilman, Igit; taufik, rahman; Sakethi, Dwi; Muhaqiqin, Muhaqiqin (JESII: Journal of Elektronik Sistem InformasI, 2025)
Testing on a system is carried out to determine whether a system that is built will run properly or if there are still bugs or errors that must be fixed. There are many methods in testing a system or software, one that is widely used by testers is the Black-box testing method. In this study the software that will be tested is an information system for the Smart Indonesia Card (KIP) Lecture Movement Ayo Lecture (GAK) recommendation information system. This information system is a system intended to provide information about the GAK program. In addition, this system is also expected to help optimize business processes in selecting applicants for KIP Lecture recommendations later. In implementing the GAK system, it is first necessary to test the system. System testing is one of the stages that cannot be eliminated in the development of a software. In testing, this system is tested using Black Box Testing in the hope of minimizing errors and ensuring that the system built has results that are in accordance with what is expected. With this test, it is expected that the quality of the software produced is in accordance with the expected function. Black-Box Testing, KIP College Recommendation, GAK Program, Information Systems